APLIKASI EKSTRAK Dioscorea hispidia PADA HAMA Pomacea speciosa DI PERTANAMAN PADI SAWAH - Virgilius W.S Rovanda Putra; Sri Wahyuni (Agriculture Faculty of Flores University, 2022)
The golden snail is a pest originating from the American continent and entering Asia as a food ingredient. Initially, these animals were used as ornamental animals and joined the rice fields through waterways. Even the golden snail is one of the main pests that attack rice plants. Utilization of gadung tuber is an alternative to controlling golden snails considering the abundant presence of gadung tuber and its toxic cyanide content. This study aims to determine the ability of gadung tuber extract to control golden snail pests, the concentration of gadung tuber extract is the best in controlling golden snail pests. The research method was arranged in a randomized block design, with 4 repetitions and 5 treatments at the yam tuber extract level, namely, G0 (0 g/5 l), G1 (3 g/5 l), G2 (6 g/5 l), G3 ( 9 g/5 l) and G4 (12 g/5 l). The application of gadung tuber extract was carried out 2 times, namely on rice plants aged 7 hst and 18 hst which were given by spraying on each research plot in the morning at 07.00-Wita. The results of the study showed that gadung tuber extract had activity as a contact, stomach, and systemic poison with the best dose being 3 grams/5 liters